PENDEKATAN SOSIOLOGIS DALAM STUDI ISLAM - Mubaidilla, Irfa'i Alfian; Mubaidilla, Trias Fatih (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
The essence of religious teachings at this time in fact needs to be understood in depth not only to be understood vaguely or only in a textual sense, but rather to the true core meaning of religion. A normative-theological understanding of religion must first be accompanied by a functional understanding of the concept of religion so that the essence of religious teachings can be used to answer problems that exist in the social aspect. The purpose of this study is to provide an explanation of how the sociological approach is in Islamic studies. This research uses a qualitative approach with a type of literature study. Sources of data from documentation are in the form of books, journals or scientific papers, as well as supporting articles. The discussion method in this study uses the description-analysis method. The problem with the current sociological approach is that the major theory that is commonly used is a contemporary sociological approach developed with a focus on Western society, so that this approach is not universal and sometimes even contradicts the perceptions of non-Western local communities. Sometimes the theory of delinquency or delinquency based on the experience and research of Western society cannot explain the problem of delinquency and delinquency in non-Western areas.